EKSPLORASI ETNOMATEMATIKA PADA RITUAL BAREMAH SUKU DAYAK BALANGIT KECAMATAN JELIMPO KABUPATEN LANDAK - Lidia, Antonia; Liliana, Sepiani (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2025)
This study aims to find out the mathematical activities contained in the baremah ritual of the Balangit Dayak Tribe in Landak Regency. Ethnomathematics is the science that studies the ways in which certain societies or cultural groups use and understand mathematics in everyday life. The type of research used is qualitative research with an ethnographic approach. The data collection techniques used in this study are observation, interviews with traditional leaders or cultural actors, as well as documentation of baremah activities, then data analysis techniques used, namely data reduction, data presentation, and conclusion drawn. The results of the study show that Baremah is one of the Dayak cultures that reflects fundamental mathematical activities: locating, counting, designing, and explaining. Each activity demonstrates the linkage between cultural values and mathematical concepts relevant to contextual learning. This analysis includes the history and stages of the ritual, as well as the preparation and execution of the ritual, all of which contain mathematical elements such as calculating, locating locations, designing, and explaining. By being aware of the cultural context and connecting it with mathematical activities, we can find out that our daily activities and the cultural diversity that we have have have activities, elements and even mathematical concepts in it. ABSTRAKPenelitian ini bertujuan untuk mengetahui aktivitas matematika yang terdapat dalam ritual baremah Suku Dayak Balangit di Kabupaten Landak. Etnomatematika adalah ilmu yang mempelajari cara-cara masyarakat atau kelompok budaya tertentu menggunakan dan memahami matematika dalam kehidupan sehari-hari. Jenis penelitian yang digunakan adalah penelitian kualitatif dengan pendekatan etnografi. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah observasi, wawancara dengan tokoh adat atau pelaku budaya, serta dokumentasi kegiatan baremah, kemudian teknik analisis data yang digunakan yaitu Reduksi data, penyajian data,  penarikan kesimpulan. Hasil penelitian menunjukkan bahwa Baremah adalah salah satu budaya Suku Dayak yang mencerminkan aktivitas fundamental matematis: locating, counting, designing, dan explaining. Setiap aktivitas menunjukkan keterkaitan antara nilai budaya dan konsep matematis yang relevan untuk pembelajaran kontekstual. Analisis ini meliputi sejarah dan tahapan ritual, serta persiapan dan pelaksanaan ritual, yang semuanya mengandung unsur matematika seperti menghitung, mencari lokasi, mendesain, dan menjelaskan. Dengan menyadari konteks budaya dan menghubungkannya dengan aktivitas matematika, kita dapat mengetahui bahwa kegiatan kita sehari-hari dan keberagaman budaya yang kita miliki itu terdapat aktivitas, unsur bahkan konsep matematika didalamnya.